Measurement of the normal mandible in neonates in east China - Jiang, Shupei; Han, Tao; Shen, Weimin (Frontiers in Pediatrics, 2023)
Objective To measure the related indicators of neonatal mandible in East China. This provides basic data for the study of mandible position and morphology of normal newborns, and can also provide data support for the diagnosis, evaluation, and treatment of Pierre Robin sequence.Methods First, we collected the CT data of normal neonates. The data included maxilla and mandible. We exported the data in DICOM format. In the second step, we reconstruct the data into a three-dimensional model. Specific measurement items were as follows: ①α: We observed the 3D model to find the left and right gonions (LGo, RGo) and the menton (Me), and used the angle measurement tool of the software to appoint Me as the apex, and connected the points LGo, Me and RGo as angle α. ② the distance between the left and right gonions: measure the distance between the bilateral gonions as a. ③ the distance from the Me to the line between LGo and RGo: The LGo and RGo were connected as a line on the 3D model, then the distance between Me and the line was measured as b. ④ the distance between the upper and lower jaw: The median sagittal view was found and the distance c between the foremost point of the upper jaw and the foremost point of the lower jaw was measured. We imported the measurement results into the SPSS software for statistical analysis.Results Specific measurement results: ① α: 86.34 ± 8.58 °. ② a: 63.63 ± 6.83 mm. ③ b: 31.99 ± 3.70 mm. ④ c: 2.28 ± 1.04 mm. Among all the above indicators, there was no statistical difference between gender.Conclusions In this study, 132 neonates were initially screened, of which 117 met the inclusion criteria and were finally included. There were 69 males and 48 females. The indicators α, a, b, and c showed no statistical differences between males and females, therefore we combined the results to obtain the normal reference value: angle α: 86.34±8.58°; distance a: 63.63 ± 6.83 mm; distance b: 31.99±3.70 mm; distance c: 2.28 ± 1.04 mm.